A retrospective study in a comprehensive assessment of the various systemic factors of Iraqi patients receiving dental implants - Mohammed, Ahmed Khamis; Soud, Samara Salman; Mohammed, Jalal Hisham (International Journal of Medical, Pharmacy and Drug Research, 2022)
In this study, 220 patients from different hospitals in Iraq and distribution Lost follow-up implants and Failed implants of the patient's study for four years, 300 implants. Study showed 220 participants were included, and the average age ranged between 40-60 years with a mean value and standard deviation of 48±7.8.0 This study was designed by adopting an analysis approach for all factors affecting dental implants, and the results were analysed according to the statistical analysis program IBM SPSS Soft. The quality of life (WHO QOL-BREF) was also measured for the purpose of conducting a comprehensive assessment of the various systemic factors of Iraqi patients receiving dental implants. The results which found to be distributed according to gender for 130 male patients with 59.09%, females for 90 patients with 40.09%, Implant insertion torque range achieved in no. of cases (Maxillary dental implants with No. of implants placed 30 for 30±4.9 N and 40 No. of implants placed with Implant insertion torque range achieved in no. of cases 45±7.7 N), (Mandibular dental implants with No. of implants placed for 40 (Implant insertion torque range achieved in no. of cases 34±3.4), (Mandibular dental implants with No. of implants placed 175 and Implant insertion torque range achieved in no. of cases 47±6.6) The effect of dental implants on the quality of life of patients was also identified, and a statistically significant relationship was found at a p-value < 0.05